Macroscopic and radiographic aspects of orthodontic movement associated with corticotomy: animal study - Zuppardo, Marcelo Lelis [UNESP]; Ferreira, Camila Lopes [UNESP]; de Moura, Nicole Berton [UNESP]; Longo, Mariellen [UNESP]; Santamaria, Milton; Lopes, Sergio Lucio Pereira Castro [UNESP]; Santamaria, Mauro Pedrine [UNESP]; Jardini, Maria Aparecida Neves [UNESP] (Springer Nature, 2019)
Introduction: To quantify the rate of tooth movement in two corticotomy protocols in an experimental model in rats through macroscopic and radiographic analysis. Methods: The animals were divided into three groups: orthodontic movement (CO), orthodontic movement plus corticotomy surgery (G2), and orthodontic movement and corticotomy surgery with decorticalization (G3).The euthanasia occurred in 7 and 14 days. The data were statistically analyzed (p < 0.05). Results: The CO presented lower distance between the mesial surface of the first molar and the distal surface of the third molar when compared to the G2 (6.96 ± 0.24, p = 0.009) and G3 (6.93 ± 0.18, p = 0.016) in the macroscopic analysis. In the 7 days, there was no statistically significant radiographic difference between the three groups: CO(0.94 ± 0.21 mm 2 ), G2(1.05 ± 0,27 mm 2 ), and G3(1.08 ± 0.27 mm 2 ).There was a statistically significant difference between CO (0.87 ± 0.12 mm 2 ), G2 (1.00 ± 0.12 mm 2 ), and G3 (1.11 ± 0.14 mm 2 ) at 14 days. There was a statistically significant linear difference between the groups in all periods. Conclusion: Tooth movement and the region of interest were influenced by corticotomy, regardless of the surgical technique in the 14 days.
Keywords: Animal model; Corticotomy surgery; Decorticalization; Orthodontic movement